Toward an Integrated Approach to Perception and Action: Conference Report and Future Directions - Gordon, Goren; Kaplan, David M.; Lankow, Benjamin; Little, Daniel Y.; Sherwin, Jason; Suter, Benjamin A.; Thaler, Lore (Frontiers in Systems Neuroscience, 2011)
This article was motivated by the conference entitled ‘Perception & Action – An Interdisciplinary Approach to Cognitive Systems Theory’, which took place September 14-16, 2010 at the Santa Fe Institute, NM, U.S.A. The goal of the conference was to bring together an interdisciplinary group of neuroscientists, roboticists and theorists to discuss the extent and implications of action-perception integration in the brain. The motivation for the conference was the realization that it is a widespread approach in biological, theoretical and computational neuroscience to investigate sensory and motor function of the brain in isolation from one another, while at the same time, it is generally appreciated that sensory and motor processing cannot be fully separated. Our article summarizes the key findings of the conference, provides a hypothetical model that integrates the major themes and concepts presented at the conference, and concludes with a perspective on future challenges in the field.